2002
DOI: 10.1002/1521-4095(20020503)14:9<651::aid-adma651>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting Polymer Nanospheres in Aqueous Dispersion Prepared by a Miniemulsion Process

Abstract: A miniemulsion process has been used to create layers of conjugated semiconducting polymers from aqueous suspensions. Layers of particles with sizes ranging between 70 and 250 nm can be formed and annealing results in coalescing of the particles into large homogeneous domains (see Figure for a photoluminescence image of a Me‐LPPP layer).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
309
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 355 publications
(313 citation statements)
references
References 16 publications
3
309
0
1
Order By: Relevance
“…The polymer chloroform droplets constitute the dispersed phase with an aqueous continuous phase. This is a modification of the usual method for generating polymer nanoparticles where the dispersed phase was liquid monomer; this alternative method was first reported by Landfester and Kietzke [17,18]. Immediately after miniemulsification, the solvent is removed from the dispersed droplets via evaporation, leaving polymer nanoparticles.…”
Section: Synthesis Of Nps Via the Miniemulsion Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymer chloroform droplets constitute the dispersed phase with an aqueous continuous phase. This is a modification of the usual method for generating polymer nanoparticles where the dispersed phase was liquid monomer; this alternative method was first reported by Landfester and Kietzke [17,18]. Immediately after miniemulsification, the solvent is removed from the dispersed droplets via evaporation, leaving polymer nanoparticles.…”
Section: Synthesis Of Nps Via the Miniemulsion Processmentioning
confidence: 99%
“…The earliest reports of semiconducting polymer nanoparticles (NPs) dispersed in water showed that conductive coatings could be prepared by mixing colloidal (10-100 nm diameter) conducting polymer in a latex base [15,16]. In 2002, work by Landfester et al showed that conjugated semiconducting polymers could be deposited from aqueous dispersions prepared by the miniemulsion process [17]. In 2003, Kietzke et al reported the first OPV devices based on nanoparticles (50-250 nm diameter) of poly(9,9-dioctylfluorene-co-benzothiadiazole (F8BT) and poly(9,9-dioctylfluorene-co-N,N'-bis(4-butylphenyl)-N,N'-diphenyl-1,4-phenylenediamine) (PFB) semi-conducting polymers.…”
Section: Introductionmentioning
confidence: 99%
“…(i) Initially, CPNs were prepared via an emulsion technique that was described by Landfester and co-workers [101][102][103][104]. The polymer solution is added into surfactant-containing water, and the mixture is sonicated for a short time until a homogeneous size distribution of the droplets is obtained in the resulting miniemulsion.…”
Section: Introductionmentioning
confidence: 99%
“…The initial PF-based nanoparticles of PF-01c (PF2/6), PF-01d (PF1112) and PF-02 (Me-ladder-type poly(para-phenylene); Me-LPPP) were prepared via the miniemulsion method by Landfester et al [104]. The sizes of the CPNs range from 50 to 250 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation